The Preconditions of Economic Management of Problematic Region in a Federal State - Viktor I. Abramov; Sofia Sh. Ostanina; Ekaterina L. Vodolazhskaya; Alexey D. Chudnovskiy; Maxim A. Suchkov; Larisa F. Zhandarova; Alla A. Rybolovleva; Guzel B. Sayfutdinova (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the need for a balanced socio-economic development of territories in a Federal state. Socio-economic development of the regions of a Federal state is inhomogeneous. Some regions, independently solving socio-economic problems is steadily growing. Other regions need support from the outside. One of the solutions to the problem is the transition to a new model of environmental development of the economy through strengthening of the system of strategic management of regional development; more integrated and balanced regional development and distribution of productive forces; reduction of territorial socio-economic differentiation to the level, conditioned by the objective differences of the regions; the balance of the revenue base and expenditure commitments of the regions. The purpose of the article is to identify prerequisites of economic management of problematic region in a Federal state. A leading approach is the institutional approach that considers the problematic region as an area that needs state support in solving the socio-economic problems. The article presents a typology of problem regions; clarifies the essence of the problem region; identifies and scientifically justifies managerial preconditions (historical-geographical, fiscal, Federative-subsidiary) of the economy of the problematic region in a Federal state. The paper submissions can be useful for specialists of Federal and regional authorities, local governments, line ministries, scholars interested in regional Economics.